Institutional governance perspectives of carbon emission disclosures among electricity companies in Asia - Alrazi B.; Bahari N.A.S.; Husin N.M.; Khalid F.M. (Science Publishing Corporation Inc, 2023)
On the basis of institutional governance perspectives, it examines internal and state factors influencing the carbon emission disclosures among 75 electricity companies in Asia. It content analysed the annual reports and stand-alone sustainability reports for the year 2013. Overall, the findings suggested that the adoption of GRI Sustainability Reporting Guidelines and a country's strength of law enforcement and commitment towards the environment had a significant influence on the extent of carbon emission disclosures. Other variables - environmental management system, environmental committee, voluntary participation in CDP programmme, corporate governance, and country's legal origin - are not significant. Considering electricity industry and Asian region are among the main contributors to the global carbon emissions, there is a pressing need for the leaders within the industry and across the countries to institute mechanisms to combat climate change including through making corporate disclosures mandatory. 2018 Authors.